MUC1/SEC and MUC1/Y overexpression is associated with inflammation in Sjögren's syndrome. (6th April 2015) - Sung, HH; Castro, I; González, S; Aguilera, S; Smorodinsky, NI; Quest, AFG; Bahamondes, V; Alliende, C; Cortés, J; Molina, C; Urzúa, U; Barrera, M‐J; et al.
<x xml:space="preserve">Abstract</x> Objectives To evaluate the expression and localization of MUC1/SEC and MUC1/Y isoforms in labial salivary glands (LSG) from Sjögren's syndrome patients (SS patients), as well as their in vitro expression induced by cytokines. Subjects and methods Labial salivary gland from 27 primary SS patients and 22 non‐SS sicca subjects were studied. Relative MUC1/SEC and MUC1/Y mRNA levels were determined by qPCR and protein levels by Western blotting. Induction of mucin mRNAs was assayed in vitro. Immunohistochemistry was used for localization. Results Relative MUC1/SEC and MUC1/Y mRNA and protein levels were significantly higher in LSG from SS patients. These mRNAs were induced by cytokines. MUC1/SEC and MUC1/Y were detected in acini apical region of control LSGs, and significant cytoplasmic accumulation was observed in acini of SS patients. MUC1/Y localized in acinar nuclei and cytoplasm of inflammatory cells of LSG from SS patients. A strong positive correlation was observed between cellular MUC1/SEC levels and glandular function determined by scintigraphy. Conclusions We show for the first time that MUC1/SEC and MUC1/Y are expressed in LSG of both SS patients and non‐SS sicca subjects. The observed overexpression and aberrant localization of MUC1/SEC and MUC1/Y and their induction by pro‐inflammatory cytokines may favor the perpetuation of the inflammatory environment that disrupts the salivary glandular homeostasis in SS patients.